TUNTUTAN KOMPETENSI BAGI APARATUR DALAM PELAYANAN PUBLIK DI DAERAH - Endang Wirjatmi Trilestari (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
Public services have become the main concern for public policy in the local governing. This is to harmonize the dynamic change of social demands with the capacity of local government to fulfill them through public services. To achieve this, it needs better competence of government apparatus as the service executor. A range of efforts directed to improve apparatus competence in the field of public service has become an endless discussion topic among scholars. Although the demand for better competence has been recorded in numerous policy documents, it does not seem that those efforts have been optimal yet. Therefore, various views on the efforts to enhance apparatus competence in delivering services to society are continuously relevant to be discussed.